A Patient with Fatal Necrotizing Fasciitis following the Use of Intra-Articular Sodium Hyaluronate Injections: A Case Report - Shanti Virupannavar; Carla Guggenheim (Case Reports in Medicine)
Introduction. Osteoarthritis, a degenerative joint disease, is a key cause of disability around the world and an ever-growing public health concern. Intra-articular hyaluronic acid viscosupplementation is used as a conservative option for osteoarthritis knee pain relief (McArthur et al., 2012; Hootman and Helmick, 2006; Huang el al., 2011). In general, the literature has shown an excellent safety profile for this treatment modality (McArthur et al., 2012; Clegg et al., 2013; Hammesfahr et al., 2003; Neustadt et al., 2005; Cohen et al., 2008; Neustadt, 2003; Jüni et al., 2007; Peterson and Hodler, 2011). Case Presentation. In this report, we describe a case of a woman who had received multiple sodium hyaluronate injections and developed severe necrotizing fasciitis near the injection site. Conclusion. We recommend that clear guidelines for clean technique be put in place for use with sodium hyaluronate injections and consideration of full sterile technique in immunosuppressed patients.